Challenges in the recruitment and retention of nurse educators : a case of Limpopo College of Nursing, South Africa - Rikhotso, Edith Tintswalo (My University, 2019)
The Limpopo College of nursing had a high vacancy rate of nurse educators. in 2014 only 74 posts out of 147 were filled. The purpose of the study was to identify challenges in recruiting and retaining nurse educators and recommend strategies to deal with the challenges. The qualitative approach was found suitable as the study intended to explore nurse educators‟ experiences and the meaning they attach to recruitment and retention. Nurse educators who have been at the campuses for a period of five years or more were the target population; purposive convenience sampling was used. Thirteen (n=13) nurse educators were interviewed in focus groups, individual interviews were conducted with ten (n=10) heads of department (HOD‟S). Thematic data analysis was used. The findings revealed that to recruit and retain nurse educators; salaries improvement, advertisement of vacated posts, proper physical infrastructure maintenance and adequate equipment provision are the strategies to implement.
Thesis (MPA.) -- University of Limpopo, 2019
Keywords: Nurse educators; Recruitment; Retaining; Employee retention -- South Africa -- Limpopo; Employees -- South Africa -- Limpopo -- Recruitment; Employee selection -- South Africa -- Limpopo; Nurse educators